Depression in older adults: May be the mass under the tip of the iceberg? (Annals of Medical Research, 2023)
Aim: Our aim was to investigate the relationship between common geriatric syndromes and depression.Materials and Methods: 515 patients over 65 years old admitted to a university hospital participated in this cross-sectional study. The Beck Anxiety Inventory (BAI), the European Quality of Life (EQ-5D), and the Pittsburgh Sleep Quality Index (PSQI) were administered to the participants in addition to the Comprehensive Geriatric Assessment. The Geriatric Depression Scale (GDS) was used to assess depressive symptoms in persons 65 years and older.Results: The mean age of the participants was 72.2±6.3 years, and 133 (24.8%) of them scored high on the GDS for depression. The non-depressed group had lower rates of sarcopenia, fewer medications, lower BAI and PSQI scores, and higher EQ-5D and Instrumental Activities of Daily Living (IADL) scores. Correlation analysis showed that the GDS score was moderately positively associated with the number of medications (r = 0.351, p =
Keywords: Depression; Anxiety; Geriatric assessment; Malnutrition; Activities of daily living